Minimally Invasive Percutaneous Plate Osteosynthesis: A Reliable Technique in the Treatment of Distal Tibia Fractures - Bisht, Rishi; Gurung, Ganesh Bahadur (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Fractures of distal tibia pose a challenge due to limited soft tissue and poor vascularity. Treatment of these injuries using minimally invasive percutaneous plate osteosynthesis (MIPPO) technique minimizes soft tissue injury and maintains the vascular integrity of the fracture fragments preserving the biological environment. The objective of the study was to assess the clinical results of MIPPO for distal tibia fractures.METHODS: This study was carried out over 16 months in a sample size of30 patients at Bir hospital, Patan hospital and Shree Birendra hospital. All patients with skeletal maturity who had sustained distal tibia fractures including Gustilo Anderson I and II were included in the study. Data was entered and analyzed by SPSS version 16.RESULTS: The mean time for bone union and full weight bearing was 14.7 weeks. There were 2 cases of ankle stiffness, 1 case of superficial skin infection and 1 case of hardware pain in the postoperative period. All patients attained functional ankle range of motion by 14th post-operative week and by 26th week mean ankle dorsiflexion was18.63 degrees and plantar flexion was 35.4 degrees. Tenny Weiss score in the final follow up had 3 patients with excellent, 14 with good results, and 13 with fair results.CONCLUSION: Minimally invasive percutaneous plate osteosynthesis offers a reliable and reproducible technique in the treatment distal tibia fractures with intra-articular or periarticular fracture extensions. This technique avoids significant complications and is associated with good functional outcome regarding the ankle range of motion.